(3TQGFY GdESdGes - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s ((3HGHG Hf eMeO GdMSfjs)
(3ChdgG (B:s
(3HSe Gddg (B...(3aEf QYGjI GdENhGf JhLH bVGA Mb GdENhGf hGdQZHI aj GdKhGH JHYK Ydi ebGHdI GdSDGd HGdLhGH hef GdCUMGH ef YQaJ ef GdEjeGf TCfg (B... (3cJGH GdWgGQI ; GdWgGQI GSe dhVhA (B...s
(3BNQgG (B:s
... (3hGdELGHI dCf Mbge aj GdYjf GdNGeSI EPG CYJbgG aj eQV GdehJ hJRhL hONd HgG UM GdYJb hGdYbO hhQKJg Ef NQLJ ef GdKdK hEf de JNQL aYdi eG eQ ef NdGa GdSGOSI (B... (3Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\123s
(3gOjI GdYGQajf (B1\254s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis